THE APPLICATION OF A ROPE FOR CONDITION PREPARATION OF BOXERS - Izet Kahrović; Benin Murić; Oliver Radenković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The skipping rope has long been used as a means for condition preparation in boxing and other fighting sports. It can be used for the warming up in the beginning of the training or it can be used for development of various motor and functional abilities, such as speed, coordination, explosiveness of the types of skips, reaction rate, agility, aerobic and anaerobic endurance, balance, rhythm, kinesthetic and proprioceptic sensitivity. In this study, there is going to be shown a set of exercises we use during trainings of young boxers in the Boxing club "Novi Pazar".